2018
DOI: 10.1097/iae.0000000000001985
|View full text |Cite
|
Sign up to set email alerts
|

Internal Limiting Membrane Peeling Versus Inverted Flap Technique for Treatment of Full-Thickness Macular Holes

Abstract: Vitrectomy associated with the inverted ILM flap technique seems to be effective surgery for idiopathic and myopic large MHs, improving both functional and anatomical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 12 publications
7
141
0
5
Order By: Relevance
“…Indeed, the flap should provide an environment to instruct the photoreceptors in order to assume correct position during the reconstruction process and finally to improve visual acuity [2]. In line with previous papers [2][3][4][5]7,15,40,41], in both groups of this study, mean visual acuity improved after ILM-flap inversion. In particular, as we previously observed, a significant improvement of functional parameters as visual acuity, retinal sensitivity, and fixation was achieved as early as one month after surgery [15], so we considered that time point as baseline in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, the flap should provide an environment to instruct the photoreceptors in order to assume correct position during the reconstruction process and finally to improve visual acuity [2]. In line with previous papers [2][3][4][5]7,15,40,41], in both groups of this study, mean visual acuity improved after ILM-flap inversion. In particular, as we previously observed, a significant improvement of functional parameters as visual acuity, retinal sensitivity, and fixation was achieved as early as one month after surgery [15], so we considered that time point as baseline in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The inverted inner limiting membrane (ILM)-flap technique has become one of the most effective procedures, with more than 90% of closure rate of LMH [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported a higher anatomical and functional success rate with this technique and its certain modifications. 8,[15][16][17][18][19] Andrew et al used a fragment of ILM, described as "ILM hinge" attached to the hole margin, which is then folded in the hole and allowed to settle at base of the hole. Michalewska et al developed a modification of the original inverted ILM flap technique, peeling only the area temporal to MH…”
Section: Inverted Ilm Flapmentioning
confidence: 99%
“…In 2010, Michalewska et al introduced the inverted ILM flap technique, improving both visual acuity and closure success of large idiopathic MHs and myopic MHs [6]. More recently, Rizzo et al found out, in a large comparative study, a 95.6% and a 88.4% closure rate respectively in idiopathic MHs > 400 μm and myopic MHs with the inverted ILM flap procedure [7].…”
Section: Introductionmentioning
confidence: 99%